Antibiofilm of metabolites of the Proteus myxofaciens JB 20B for the prevention and treatment of vaname shrimp infected with Vibrio harveyi bacteria - Nanda Tri Rezeki; Dinamella Wahjuningrum; Widanarni Widanarni; Diana Elizabeth Waturangi (Jurnal Akuakultur Indonesia)
Vibrio harveyi is one of the common bacteria that cause disease in vaname shrimp. The purpose of this study is to determine the efficacy of bacterial metabolites Proteus myxofaciens JB 20B as an antibiofilm agent in the prevention and treatment of V. harveyi-infected vaname shrimp (Litopenaeus vannamei).  The research design included eight treatments and three replicates: K- (negative control), K+ (positive control), KANC and KANG (antibiotic control 50 g/100ml for preventive and treatment), PCE (preventive extract 0.1 ml/Kg feed), PCS (preventive supernatant 20 ml/Kg feed), PGE (treatment extract 0.1 ml/Kg feed), and PGS (treatment supernatant 20 ml/Kg feed). On day 15th, vaname shrimp were intramuscularly infected with 106 CFU/mL of V. harveyi. Examining clinical symptoms, viewing histology, assessing total haemocyte count, phagocytosis activity, phenoloxidase activity, respiratory burst, and growth performance. According to the findings of this study, the treatment of bacterial metabolites P. myxofaciens JB 20B (PCE, PCS, PGE, and PGS) is superior to the positive control (K+) treatment in terms of reducing shrimp hepatopancreas necrosis, increasing the value of total haemocyte count, phagocytosis activity, phenoloxidase activity, respiratory burst, and growth performance of vaname shrimp through post-infection feeding in both prevention and treatment. The use of P. myxofaciens JB 20B bacterial metabolites to control V. harveyi infection in vaname shrimp yielded the best results in the supernatant treatment.